Pengaruh Variabilitas Iklim Terhadap Kesesuaian Lahan Lada (Piper nigrum L.) Berbasis Analisis Spasial di Kepulauan Bangka Belitung - Fatrina Aprilia Sari; Mokhamad Yusup Nur Khakim; Budhi Setiawan; Presli Panusunan Simanjuntak (BPFP Universitas Bengkulu, 2025)
[SPATIAL ANALYSIS OF THE IMPACT OF CLIMATE VARIABILITY ON LAND SUITABILITY POTENTIAL FOR BLACK PEPPER (Piper nigrum L.) Cultivation In The Bangka Belitung Islands]. The Bangka Belitung Islands are a major center of pepper production in Indonesia; however, over the past decade, cultivated area and productivity have declined due to climate variability and limited land biophysical information. This study aims to analyze land suitability for pepper (Piper nigrum L.) cultivation based on climatic, topographic, and soil indicators, as well as to evaluate the effect of climate variability on changes in land potential across the island region. The data used include rainfall observations from 71 rain gauges during 2014–2023, ERA5 reanalysis data for surface temperature, humidity, and solar radiation, and maps of slope and soil types as physiographic parameters. All parameters were processed using a Geographic Information System with the Inverse Distance Weighting (IDW) interpolation method to generate the spatial distribution of climate variables, while a weighted overlay method was applied to determine land suitability classes. Validation was conducted by comparing ERA5 data with observational data to ensure the consistency of spatial climate patterns. The results indicate that climate variability contributes to a decline in land suitability in coastal areas with soil textures that are sensitive to environmental changes. Most of the area, covering 1,189.76 ha, is classified as Highly Suitable (S1) and is distributed in central Bangka Island and parts of Belitung Island. Meanwhile, 452.65 ha are classified as Moderately Suitable (S2) and are predominantly located in coastal areas with soil limitations and coastal environmental influences. These findings highlight the importance of climate adaptation strategies to support sustainable national pepper cultivation. Full txt pdf